Exploring students' visualisation competence with photomicrographs of villi. Issue 14 (22nd September 2021) - Cheung, Kason Ka Ching; Winterbottom, Mark
ABSTRACT: Photomicrographs are representations of small-scale entities. It has been long argued that students can be weak in perceiving microscopic entities compared to macroscopic entities. However, only a small body of research has investigated how students utilise photomicrographs to make sense of biological phenomena. This study uses a theoretical construct, 'visualisation competence', to explore students' skills and practices in utilising photomicrographs. Fifty UK students' visualisation competence with photomicrographs of villi were measured by open-ended questionnaires. Content analysis showed a wide range of students' performance in all components of visualisation competence with photomicrographs, namely constructing, interpreting, transforming and critiquing. Students' performance on sub-components within each skill component of visualisation competence for the photomicrograph of villi were also analysed. The mean scores of constructing a biological diagram resembling the photomicrograph and critiquing whether a representation resembles the photomicrograph were higher than that of interpreting the photomicrograph. Transforming the longitudinal section of photomicrographs into the transverse section had the lowest score among all four skill components. Moreover, the sub-components which rely heavily on textual processing were found to be significantly correlated with each other. Implications for teaching and learning of photomicrographs were discussed.